Problems and Legal Implications of Interfaith Marriage in Indonesia - Mardani Mardani (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2026)
Interfaith marriage in Indonesia constitutes a complex legal issue arising from the tension between religion-based legal norms and the realities of a pluralistic society. Although Law Number 1 of 1974 provides that the validity of a marriage is determined by religious law, interfaith marriages continue to occur and give rise to legal uncertainties, particularly regarding registration, legal recognition, and the protection of civil rights. The issue has become increasingly significant following the issuance of Supreme Court Circular Letter Number 2 of 2023, which restricts the registration of interfaith marriages and contributes to normative disharmony and inconsistencies in judicial practice. This study employs a normative legal research method using statutory, conceptual, and case approaches. Legal materials are analyzed through prescriptive and evaluative methods, supported by grammatical, systematic, and teleological interpretations. The findings indicate that the absence of explicit regulation governing interfaith marriage has created legal gaps and normative conflicts, thereby necessitating the reconstruction of legal norms that integrate religious principles with human rights perspectives. Accordingly, the development of an adaptive and responsive legal framework is essential to ensure legal certainty and justice within a pluralistic society.